Modification Of Chitosan With Deep Eutectic Solvent For The Adsorption Of Malachite Green - Chadi, Sadiq Abubakar (2022)
The presence of dye in environmental wastewater is a serious concern as it poses a threat to the ecosystem. This thesis provides background information about different techniques to remove malachite green (MG) from an aqueous medium. Various treatment technologies have been studied to remove dye, adsorption and semi-permeable membrane extraction using polymer inclusion membrane (PIM). These methods are considered efficient methods for the decontamination of dyes from wastewater in this study. Chitosan (CH) is considered a promising, readily available, and inexpensive adsorption material obtained as a by-product from the seafood industry and other sources. Meanwhile, CH was functionalised and used as an adsorbent. CH was functionalised with using deep eutectic solvents (DES) to syntheses beads, magnetic nano-sized particles and was used as extractants and plasticisers at a different ratio. DES such as bis-(2-Ethylhexyl) phosphate (B2EHP), Aliquat 336, and dioctyl phthalate (DOP) were used to prepared PIMs. Various techniques such as pH point of zero charge (pHpzc), solubility, scanning electron microscopy (SEM), energy dispersion X-ray (EDX), vibrating sample magnetometry (VSM), transmission electron microscopy (TEM), thermo gravimetric/differential thermal analyses (TGA/DTA), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Brunauer-Emett-Teller (BET) were carried out to analyse the physicochemical characteristics of the newly prepared CH materials. The characterisation analysis has shown surface modifications, incorporated B2EHP, DOP, Aliquat 336, iron, and chloride ions onto the CH molecules.